(untitled) - De Wet Rautenbach, Cornelis Johannes

Implications of the new air quality bill on the management of H2S emissions from Sasol’s operations in Secunda, South Africa (2013)
Dissertation (MSc (Society and Environment))--University of Pretoria, 2005.